Comparison of agricultural extension during the covid-19 pandemic in various countries (meta-synthesis) - Btari Prabasini; Birendra Kumar; Siti Azizah (Faculty of Animal Science, Universitas Brawijaya, 2021)
The objective of this study was to compare agriculture extension in different countries during the pandemic COVID-19 era. The study was conducted by comparing agricultural extensions in Africa, the United States, India, and Indonesia. Data were obtained from journals, scientific articles, and scientific reports. The source of data was collected and selected by the characteristic of inclusion. According to the characteristic of inclusion 7 sources of data were obtained and analyzed using systematic review and meta-synthesis method. Extraction source of data shows that agriculture extension in various countries experiencing different challenges due to the COVID-19 pandemic era, such as mobility restriction, differences of agriculture system, lack of facilities, false information spreading and lack of extension worker and farmers’ ability to access the internet. Due to mobility restrictions, many countries choose ICT (information and communication technology) as a new method and media for advisory service during the pandemic. The majority of the country used simple apps for farmers like Whatsapp, virtual meetings via zoom, website, and YouTube. Most countries switched to cyber extensions to prevent the virus from spreading. India and Africa increase their extension facilities and provide Q&A (question and answer) platform that is easy to use by farmers. Developing countries like Africa, India, and Indonesia provide training for extension agents to improve their ability to access the internet and gadgets, thus, they can improve their ability and provide knowledge to the farmers durin pandemic.